L’interférence chez les étudiants en philologie italienne en tant que défi pour l’enseignant - Karczewska, Małgorzata (Studia Romanica Posnaniensia, 2011)
Polish students of Italian philology in Poznań study two Romance languages: Italian and French, which on one hand facilitates the process of learning, as many rules of grammar and words are similar in both languages. On the other hand, though, the closeness of two linguistic systems is the source of the interference phenomenon even if none of the languages is a mother tongue. As students of philology are expected to speak perfectly the foreign language studied, all mistakes need to be eliminated. In the present paper we concentrate on mistakes made in Italian due to the interference of French. After a short theoretical introduction on interference we give some examples of errors to illustrate the phenomenon and to show the areas in which errors are particularly numerous. In the third part of the paper we suggest some solutions which are based on observations and conclusions resulting from the professional experience as a lecturer in Italian.